Knowledge and Attitudes of Midwives Concerning the Interpretation and Use of Cardiotocographs in Jordan - Arwa Alsaraireh; Dalal Yehia; Atika Khalaf (Journal of Holistic Nursing and Midwifery)
Introduction: A midwife needs to know how to assess fetal heart rates, recognize and interpret fetal heart patterns, report any substandard patterns, and initiate supportive measures as necessary. Objective: This study aims to assess the knowledge and attitudes of midwives concerning the interpretation and use of cardiotocographs. Materials and Methods: This cross-sectional study involves 183 midwives working in maternity units across all Jordanian regions. An online survey was used to collect data, including 6 demographic questions, 10 questions about knowledge, and 25 questions about attitude. The data were analyzed using descriptive statistics (Mean±SD, No. [%]), ANOVA, and the Pearson correlation tests. The significance level was set to be <0.05. Results: Most participants were 21 to 30 years old, and most midwives (59.6%) had no more than six years of experience. The result showed that the total scores for the knowledge and attitude regarding cardiotocographs (CTGs) interpretation and usage were 68.7% and 73.0%, respectively. There is a significant relationship between the knowledge about the interpretation and use of CTGs and the years of experience (P=0.003), with higher knowledge scores among midwives with fewer than 6 years of experience. Furthermore, there is a significant relationship between the knowledge of CTGs and level of education (P=0.002), indicating higher knowledge scores among midwives with a degree. The knowledge about classifying the CTG traces was significantly correlated with the region of work (P=0.018), with higher scores among midwives from the southern region. Finally, there was a positive correlation between knowledge and attitude (r=0.007, P<0.05). Conclusion: Based on the study result, the participant’s knowledge and attitudes are not satisfactory; thus, comprehensive education and training should be prioritized to improve midwives’ knowledge and attitudes toward using cardiotocograph.